Pengaruh Persepsi Harga, Kualitas Produk, Citra Merek, Desain Produk, dan Faktor Lainnya terhadap Keputusan Pembelian Konsumen: Literature Review - Kisworo, Endro (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This literature review discusses the influence of various marketing factors on purchase intention and consumer buying decisions, focusing on price perception, product quality, brand image, product design, and several other factors. The review is based on 10 recent empirical studies. The findings indicate that, in general, price perception and product quality consistently have a significant positive effect on both purchase intention and consumer buying decisions. Brand image also tends to have a strong positive impact, although in certain contexts, its influence can be negative. Attractive product design generally increases consumers’ purchase desire, but its effect varies depending on consumer preferences. Other factors such as product features, product innovation, consumer preferences, perceived value, and promotional strategies also play a role in influencing consumer decisions. This synthesis concludes that companies should pay close attention to product quality and fair pricing, build a positive brand image, and design products with features that align with market preferences. Differences in study results indicate that the impact of these factors may vary depending on the product context and consumer segment.